Nitrogen Fertilization and Wheat Variety Interact with Environment Independently to Determine Wheat Yield in Kansas - N. Giordano; R. P. Lollato (Kansas Agricultural Experiment Station Research Reports, 2022)
Both nitrogen (N) management and variety selection are crucial elements that influence wheat yield; however, there is limited research exploring whether wheat varieties differ in their response to N rate. Thus, our objectives were to determine potential variety by N rate interactions among modern winter wheat varieties. Factorial field experiments were established in four Kansas locations during the 2020–2021 growing season, including two fields near Ashland Bottoms, one field near Hutchinson, and one near Manhattan. Whole plot treatments were four N rates (0, 40, 80, and 120 lb N/a) applied in the spring and subplots were 14 commercially available winter wheat varieties. Initial soil NO3-N in the 0- to 24-in. soil profile at sowing ranged from 45 to 67 lb N/a. The weather conditions were overall favorable for crop yields across all studied environments. Wheat grain yield response to the spring-applied N fertilizer depended on location, ranging from 0.1 to 0.5 bushel per lb of N applied, with greater responses to the first 40 to 80 pounds of N per acre in three out of four environments. Likewise, variety grain yield depended on location, and varieties ranking changed accordingly. However, there was no variety by nitrogen interaction, suggesting that all varieties responded similarly to the applied N.
Keywords: genotype; nitrogen rate; precipitation; Triticum aestivum L.; winter wheat